Matrix Metalloproteinase-9 Relationship With Infarct Growth and Hemorrhagic Transformation in the Era of Thrombectomy - Mechtouff, Laura; Bochaton, Thomas; Paccalet, Alexandre; Crola Da Silva, Claire; Buisson, Marielle; Amaz, Camille; Bouin, Morgane; Derex, Laurent; Ong, Elodie; Berthezene, Yves; Eker, Omer Faruk; Dufay, Nathalie; et al. (Frontiers in Neurology, 2020)
Objective To assess the relationship between matrix metalloproteinase 9 (MMP-9), a proteolytic enzyme involved in the breakdown of the blood-brain barrier, and infarct growth and hemorrhagic transformation in ischemic stroke with large vessel occlusion (LVO) in the era of mechanical thrombectomy (MT) using the kinetics of MMP-9 and sequential magnetic resonance imaging (MRI). Methods HIBISCUS-STROKE is a cohort study including patients admitted for an ischemic stroke with LVO treated with MT following admission MRI. Patients underwent sequential assessment of MMP-9, follow-up CT at day 1 and MRI at day 6. The CT scan at day 1 classified any hemorrhagic transformation according to the European Co-operative Acute Stroke Study-II (ECASS II) classification. Infarct growth was defined as the difference between final Fluid-Attenuated Inversion Recovery volume and baseline diffusion-weighted imaging volume. Conditional logistic regression analyses were adjusted for main confounding variables including reperfusion status. Results Between 10/21/2016 and 04/12/2019, 148 patients met the inclusion criteria. A high MMP-9 level at 6 hours from admission (H6) (p=0.02), a high glucose level (p=0.01), a high temperature (p=0.04) and lack of reperfusion (p=0.02) were associated with infarct growth. A high MMP-9 level at H6 (p=0.03), a high glucose level (p=0.03) and a long delay from symptom onset to groin puncture (p=0.01) were associated with hemorrhagic transformation. Conclusions In this MT cohort study, MMP-9 level at H6 predicts infarct growth and hemorrhagic transformation.